Calculus Formation: Nurses' Decision‐Making in Abortion‐Related Care. Issue 3 (27th March 2015) - McLemore, Monica R.; Kools, Susan; Levi, Amy J.
Abstract Nurses routinely provide care to patients in ethically challenging situations. To explore the continuum between conscientious objectors and designated staff in the provision of care to women seeking abortions, the aim of this study was to thickly describe decision‐making, using abortion as the clinical context to elucidate how nurses approach ethically challenging work. A purposive sample of 25 nurses who worked in abortion clinics, emergency departments, intensive care units, labor, and delivery, operating rooms, and post anesthesia care units were interviewed. Qualitative description and thematic analysis were used to identify the cognitive, emotional, and behavioral processes in nurses' decisions to care for women needing abortions. Nurses developed and used multifaceted, real‐time calculi when making decisions about their participation in emergent or routine abortion care. Nurses tacked back and forth between the personal and professional and/or held multiple contradictory positions simultaneously. Nurses weighed the role and opinion of others to determine if they know how to or know why they would provide abortion care to women, particularly in the elective abortion context. The parameters of the nurse–patient relationship were complex and specific to the experiences of both the nurse and patient. Findings from this study further develop the science of ethically challenging decision‐making and expand our understanding of factors that influence how nurses develop relationships to ethically challenging work. © 2015 Wiley Periodicals, Inc.